Lolium multiflorum (ryegrass) diet modifies the productive response and enhances the meat of grass carp (Ctenopharyngodon idella Val.) with omega 3 fatty acid beneficial to human health - Montenegro, Luciano Federico; Garcia, Pilar Tere; Descalzo, Adriana Maria; Perez, Carolina Daiana (Taylor & Francis, 2022)
Registered in England & Wales No. 3099067